Self-represented, Querulant or Vexatious Litigants: Two Sides of a Story - Ogawa, Megumi (Victoria University of Wellington Law Review, 2025)
Effective and efficient management of unrepresented litigants has long been a challenge for the Australian legal system. Numerous studies have already been undertaken on this topic by judges, legal practitioners and law academics resulting in various proposals for management strategies to deal with unrepresented litigants. However, those efforts were made in a marked absence of research from unrepresented litigants’ viewpoints, in particular, unrepresented litigants’ perceptions of the court’s conduct and the reasons for unrepresented litigants’ reactions to the court’s conduct. I argue that this knowledge gap has limited the effective management of unrepresented litigants. In this article, I describe the unrepresented litigant’s thoughts and actions in litigation in order to demonstrate that taking them into account will enable better management of unrepresented litigants.